A parametric analysis of factors that determine head injury outcomes following equestrian fall accidents. Issue 3 (4th May 2021) - Clark, J. Michio; Adanty, Kevin; Post, Andrew; Hoshizaki, T. Blaine; Annaidh, Aisling Ni; Gilchrist, Michael D.
Abstract: This study examined the effects and interaction of four primary impact parameters (impact velocity, angle of impact relative to the ground, ground compliance and helmet impact location) on head kinematics and brain tissue response for falls that are most commonly associated with equestrian sports. A helmeted headform was subject to parametric tests using a rail guided launcher at three impact velocities (6, 9 and 12 m/s), four angles of incidence (15°, 30°, 45° and 60°), three ground compliance levels (High, Medium and Low) and three helmet locations (front, front-boss and rear-boss). Head kinematics were obtained from the headform and a finite element model was used to estimate brain tissue response. Velocity and angle had the largest effects on the risk of concussion, as measured by head kinematics and brain tissue response, while compliance and location were less influential. Interactions such as angle and compliance were found to greatly influence the risk of concussion. These findings suggest that an increased ground compliance can decrease linear acceleration and Head Injury Criterion (HIC) but not necessarily decrease rotational kinematics and brain tissue response. Consequently, the use of technological designs to attenuate rotational acceleration and decouple the helmet from that of the head may provide better safety than simply the addition of extra protective layers to the ground or a helmet liners.